2014
DOI: 10.1007/s13277-014-2088-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of LEP A19G polymorphism with cancer risk: a systematic review and pooled analysis

Abstract: The results from the published studies on the association between leptin (LEP) genetic polymorphism and cancer risk are conflicting. The common A19G (rs2167270) genetic polymorphism has been reported to be functional and may contribute to genetic susceptibility to cancers. However, the association between LEP A19G (rs2167270) genetic polymorphism and cancer risk remains inconclusive. To better understand the role of LEP A19G (rs2167270) genetic polymorphism in global cancer, we conducted this comprehensive met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Some studies have observed associations of the A allele of LEP rs2167270 –the reference allele in our study–with elevated leptin levels [ 24 , 55 ]. Contradictory to what we would then expect given the proposed directional effect, several studies have reported significant association of the A allele of this variant with decreased CRC risk [ 39 , 40 ]. Consistent with these observations, our study observed that the G allele of this variant was associated with a modest increased CRC risk among women.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have observed associations of the A allele of LEP rs2167270 –the reference allele in our study–with elevated leptin levels [ 24 , 55 ]. Contradictory to what we would then expect given the proposed directional effect, several studies have reported significant association of the A allele of this variant with decreased CRC risk [ 39 , 40 ]. Consistent with these observations, our study observed that the G allele of this variant was associated with a modest increased CRC risk among women.…”
Section: Discussionmentioning
confidence: 97%
“…DNA polymorphism in the leptin gene is associated with tumorigenesis of multiple cancer types, such as lung cancer, lymphoma, thyroid cancer, and colon cancer ( Slattery et al, 2008 ; Liu et al, 2014 ; Unsal et al, 2014 ; Marcello et al, 2015 ). LEP is primarily expressed in differentiated adipocytes of white adipose tissue, and the hormone leptin it encodes for, plays a role in the regulation of food intake and the expression of energy-regulating peptides.…”
Section: Gender Dimorphism In Adipocyte Metabolismmentioning
confidence: 99%
“…Some previous meta-analyses suggested that LEP rs7799039 A>G and rs2167270 G>A variants conferred risk to cancer. 15 – 17 However, the association of LEP rs7799039 A>G and rs2167270 G>A polymorphisms with HCC risk is unknown.…”
Section: Introductionmentioning
confidence: 99%